Doorjambs of the Garbhagriha of the Kaner-ki-Putli Temple - Temples of India Project Team (Jio Institute, 2024)
The antarala (vestibule or antechamber) of the Kaner-ki-Putli Temple leads to its garbhagriha (sanctum sanctorum), which features an intricately decorated multi-shakha (vertical bands or architraves) doorframe. It is a saptashakha (seven vertical bands) doorframe. The lower section of the doorframe depicts figures, and the upper part is embellished with a variety of decorative patterns.